Assessment influence on peak power output and road cycling performance prediction - Smith, M. F. (International Journal of Sports Science and Coaching, 2008)
The influence of cycling assessment on peak power output and road-based cycling performance prediction was evaluated in twelve well-trained amateur cyclists (mean ± SD; age, 35 ± 8 yr; body mass, 74.1 ± 6.7 kg; stature: 181 ± 6 cm). Determining peak power output, cyclists completed a graded i) ramp assessment on a Kingcycle air-braked ergometer (PPOKING), ii) continuous assessment on a SRM electromagnetically-braked ergometer (PPOSRM), and iii) discontinuous assessment on a Monark friction-braked ergometer (PPOMON). Furthermore, a 40-km road-based individual cycle race was completed. Throughout each, power was measured using an SRM Training System. Despite no differences (p > 0.05) in VO2peak across graded assessments, PPOKING (387 ± 49W) was 3.6% higher (p < 0.05) than PPOSRM (373 ± 38W) and 9% higher (p < 0.05) than PPOMON (352 ± 41W). Relating assessment-derived peak power output with road-based performance (mean power: 288 ± 36W; mean time: 62:00 ± 3:13 min:sec), PPOKING(r = 0.94: p < 0.001), PPOSRM (r = 0.87; p< 0.001) and PPOMON (r = 0.90; p < 0.001) were strongly correlated to mean power, but not time (PPOKING; r = -0.41; p > 0.05: PPOSRM; r = -0.42; p > 0.05: PPOMON; r = -0.41: p > 0.05). Independent of determination, peak power output was strongly related to performance power and may provide effective means of obtained training and racing intensities.